VASCULAR BED PECULIAR PROPERTIES IN PATIENTS WITH ISCHEMIC HEART DISEASE AND ARTERIAL HYPERTENSION. ROLE OF ANTIPLATELET THERAPY - L. A. Haisheva; S. V. Shlyk (Столичная издательская компания, 2016)
Aim. To study state of vascular wall within different levels of vascular bed in patients with arterial hypertension (HT) and ischemic heart disease (IHD), and the possibility of the correction of revealed disorders with antiplatelet agent - clopidogrel 75 mg/day. Material and methods. 40 patients with HT of 1-2 degree and IHD (stable angina of I-II functional class) were included into the study. 20 healthy volunteers were included into the control group. Pulse wave velocity (PWV) was evaluated by volumetric sphygmography. Microvasculature (MC) was evaluated by computerized ultrasound Doppler velocimetry. Plasma activity of von Willebrand factor (vWF) was evaluated by direct quantitative enzyme-linked immunosorbent chemical analysis. Results. Patients with HT and IHD have abnormalities of all levels of the vascular bed compared with subjects of control group: endothelial function (increased vWF), MC disorders (lack of the linear flow velocity augmentation 1.4% vs 23.7%), as well as increase in PWV in elastic type vessels (13.27±0.53 vs 8.37±0.76 m/s). Strong positive correlation (r=0.71; p<0.05) between HT duration and average linear velocity of blood flow was detected. Disease duration had direct correlation with MC disorders and PWV. There is correlation between MC changes and PWV in elastic vessels. Increase in vWF (168.7±9.1%) was detected in 28 (70%) patients of the main group. Blood flow velocity augmentation >20% during the test was observed in 27 (67.5%) patients treated with clopidogrel. Conclusion. Clopidogrel has effects on MC disorders and significantly reduces the vWF activity level.